REVIEW: S. Aureli, B. Battistoni, F.M. Cesaroni (a cura di), Percorsi evolutivi e soluzioni strategiche per la continuità aziendale, FrancoAngeli, Milano, 2019. - Palazzi, Federica (Piccola Impresa / Small Business, 2020)
The book provides food for thought and illustrates operational tools to face the generational shift, a particularly critical phase that involves and puts family businesses at risk. The first part of the work focuses attention on the peculiarities of family businesses and on the factors that can influence business continuity in the long term. Additionally, the critical issues of the succession process are analyzed, the phases of this process, and the protagonists, as well as the role of consultants, as privileged subjects in close contact with entrepreneurs who could effectively support the generational change. The second part is dedicated to success stories, that is, to stories of small and medium-sized enterprises or professional firms that have been able to deal with the generational shift, even taking the opportunity of succession to start an evolutionary path.